2000
DOI: 10.1093/ndt/15.9.1399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐flux dialysis on the anaemia of haemodialysis patients

Abstract: This study showed no difference in haemoglobin level increase between patients treated for 3 months with a high-flux biocompatible membrane in comparison with those treated with a standard membrane. When patients are highly selected, adequately dialysed, and have no iron or vitamin depletion, the effect of a high-flux membrane is much less than might be expected from the results of uncontrolled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 23 publications
2
46
1
4
Order By: Relevance
“…Our findings are in line with the results of a shorter-term study from Locatelli and colleagues (12). In that multicenter randomized, controlled trial the investigators could not detect differences in hemoglobin levels or ESA doses between patients treated for 3 months with a high-flux membrane compared with those treated with a standard (i.e., low-flux) membrane (12).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are in line with the results of a shorter-term study from Locatelli and colleagues (12). In that multicenter randomized, controlled trial the investigators could not detect differences in hemoglobin levels or ESA doses between patients treated for 3 months with a high-flux membrane compared with those treated with a standard (i.e., low-flux) membrane (12).…”
Section: Discussionsupporting
confidence: 90%
“…In that multicenter randomized, controlled trial the investigators could not detect differences in hemoglobin levels or ESA doses between patients treated for 3 months with a high-flux membrane compared with those treated with a standard (i.e., low-flux) membrane (12). As was seen in our study, patients in the study by Locatelli and colleagues were all adequately dialyzed and had no iron deficiency.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…However, clearance of middle and large molecules is considerably inadequate in HDF or OL-HDF. These middle and large molecular uremic toxins include protein-bound toxins or toxins whose molecular weight exceeds the pore size of the membrane used, say, β-2 microglobulin (β2M), tumor necrosis factor (TNF)-α, interleukins, complement factor D, and other pro-inflammatory factors [7,8,10,11] .…”
Section: Hf-hd and Hdfmentioning
confidence: 99%
“…53 Evidence of the clinical validation of the role of uremic inhibitors of erythropoiesis comes from numerous reports that inadequate dialysis in patients sustained by either HD or continuous ambulatory peritoneal dialysis was associated with a poor response to EPO (persistently low Hb). [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Several studies have also shown that Hb levels increased with an increase in HD dose in EPO-treated patients with low Hb. 26,62,69,74,75 In fact, the strong relation between Hb and adequacy of dialysis in patients with ESRD treated with EPO has been corroborated by analyses of pooled data at both the dialysis facility and the ESRD Network levels.…”
Section: Do Uremic Inhibitors Of Erythropoiesis Modulate Response To mentioning
confidence: 99%